Anti-Wear Characteristics of SiC Preform Reinforced AZ91 Magnesium Matrix Composites Fabricated by Cold Chamber High-Pressure Die Casting - Kucukyildirim, Bedri Onur; Vanli, Ali Serdar; Akdogan, Anil (SPRINGER INT PUBL AG, 2024)
Silicon carbide (SiC) preform reinforced magnesium (Mg) matrix composites were fabricated by the infiltration of matrix material into a SiC ceramic preform by a cold chamber high-pressure die casting (HPDC) process. All steps of the composite fabrication process are explained, and surface characterizations related to the wear properties of fabricated materials were realized. Wear tests were conducted using a ball-on-disc wear testing device at room temperature under dry sliding conditions. Specific wear rates were calculated using the disk wear loss, which was determined by measuring the wear track width. Wear surfaces were examined using scanning electron microscopy (SEM) equipped with energy-dispersive X-ray spectroscopy (EDS). The results show us that the wear resistance of composites improved and that the most effective wear mechanism is scuffing, which is a type of abrasive wear. In addition, a remarkable increase in surface properties was confirmed using hardness measurements and atomic force microscopy (AFM) investigations.
Keywords: metal matrix composites; preform; infiltration; die casting; wear testing; WEAR BEHAVIOR; MECHANICAL-PROPERTIES; ALLOY; HARDNESS; B4C; Metallurgy & Metallurgical Engineering